(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Olympic Games, a pinnacle of athletic competition and global unity, have long been a platform for showcasing human achievement. While historically dominated by male participants, the inclusion of women in the Games has marked a significant stride towards gender equality. This research paper explores the evolution of women’s participation in the Olympic Games, focusing on the breaking of barriers and the setting of records in various disciplines. The study investigates the socio-cultural, economic, and political factors that have shaped the trajectory of women’s involvement in the Games and analyzes the profound impact of their achievements on global perceptions of gender roles and athletic capabilities. The negative discourse surrounding women in sports arises from society’s failure to recognize women as individuals. Historically, and in certain regions today, women have been perceived as possessions of men, lacking a significant role in society. While gaining entry into the Olympics marked a positive step for women globally, it represented only a modest stride towards equality. Women still faced restrictions on the events they could participate in, limitations on their training and coaching, and even constraints on their attire. This article will explore the theme of female inclusion and involvement in Olympic athletics, examining the initial challenges they faced and the roles played by sports institutions, international federations, and the International Olympic Committee